Menumbuhkan Sikap Empati Melalui Pendidikan Karakter Berbasis Kearifan Lokal pada Sekolah Berasrama (Al Ulya: Jurnal Pendidikan Islam, 2019)
Education is a means in an effort to humanize humans. Education is ameans of transmission and transformation of knowledge and values. In instillingand developing the nation's character, educational institutions have an importantrole in laying the foundation of morals and personality. Empathy must bedeveloped as an effort to prevent disintegration in Indonesia. One way is to lay thefoundation of moral and character education. The purpose of this study is tocomprehensively analyze the cultivation of empathy through character educationbased on local wisdom in boarding schools. This research was conducted at twoboarding schools in Bojonegoro district, namely Ar-Rosyid Islamic BoardingSchool and At-Tanwir Islamic Boarding School. Based on the analysis of interview,observation and document data, it was found that both Islamic boarding schoolshad carried out character education based on local wisdom as an effort to instillempathy in Santri with approaches in accordance with the characteristics of eachIslamic boarding school.